The Effectiveness of visual -graphic presentation on the oral health knowledge, attitude, and practices of 10-11 years old school children in Gatid Elementary School in Santa Cruz, Laguna - Cruz, Angela Roan T.; Rebueno-Santos, Jessica K. (Manila Department of Community Dentistry, University of the Philippines Manila, 2019)
INTRODUCTION: Dental caries remains to be the leading oral health disease in the Philippines (WHO, 2012) despite it being a preventable disease. Seventy-five percent of children as young as twelve years old in the Philippines have dental caries (NMEDS, 2011). A total of 87.4% Filipinos experience dental caries. Studies have shown that dental caries can be effectively reduced by tooth brushing (NIH, 2016). Hence, knowing about proper oral health care is important in reducing the high number of Filipinos suffering from dental caries. The study aimed to determine the effectiveness of visual graphic presentation as an oral health education material on the oral health knowledge, attitude and practices of 10-11 years old schoolchildren in Gatid Elementary School in Sta. Cruz, Laguna.
METHODS: One hundred forty-three Grade 5 pupils of Gatid Elementary School participated in the study. The participants received a self-administered pretest questionnaire and checklist to measure their oral health knowledge, attitude, and practices as the baseline data. The participants were asked to watch a visual-graphic presentation about proper toothbrushing method (Modified Bass Technique) and basic oral health information for three consecutive days. After showing the video to the participants on the 3 rd day, a self-administered post test and checklist of their oral health knowledge, attitude and practices post-intervention was given. To determine if there were changes in students? oral health knowledge, attitude and practices after their exposure to the visual graphic presentation, marginal homogeneity test were utilized. This is an extension of McNemar test since there are three possible categories ? poor, medium and high, a nonparametric equivalent of paired t-test. If the p-value is less than the alpha of 0.05, researcher can conclude that there is a difference in their scores before and after the intervention.
RESULTS: The p-value obtained from the pretest and post test?s over-all results for the oral health knowledge, attitude and practices are extremely statistically significant at p=.05 level of significance. There is an increase in the post test results of the mean, median and mode, and in the minimum and maximum scores. At baseline, majority of the participants belonged to the ―Medium Knowledge‖ (44.06%) and ―Medium Attitude‖ (49%). After the intervention, 86.71% of the participants belonged to the ―High knowledge‖, and 88.81% of the participants belonged to the ―High Attitude.‖ The result on the oral health practice shows that majority of the participant belonged to the ―High Practice‖ category before and after the intervention (87 % and 98%, respectively).
CONCLUSION: This study indicated that the Visual-Graphic Presentation was effective as an oral health education material in increasing the 1) knowledge, 2) attitude, and 3) practices of the Grade 5 pupils in Gatid Elementary School.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila
Keywords: Visual graphic; School Children--Dental care--Santa Cruz, Laguna; Dental caries